Pembatalan Perjanjian Pengikatan Jual Beli Cacat Formil Melalui Gugatan Rekonvensi: Studi Putusan Nomor 1263/Pdt.G/2023/PN Dps - Retnaningsih, Heni; Setiawan, I Ketut Oka (SIGn Jurnal Hukum, 2025)
Legally defective preliminary sales agreements frequently trigger complex land ownership disputes. This research analyzes the legal reasoning (ratio decidendi) of the Panel of Judges concerning the annulment of a preliminary sales agreement due to formal defect through reconvention, utilizing Decision Number 1263/Pdt.G/2023/PN Dps as a case study, and examines the strategic function of reconvention in achieving legal certainty. Employing a normative legal research method through a case study approach and qualitative analysis of the decision data, it was found that the Panel of Judges annulled Deed of Agreement Number 18 based on the absence of valid consent (Article 1320 of the Civil Code), resulting from fictitious factual representation concerning the presence of a party. Additionally, the Deed of Power of Attorney Number 19 was declared null as it contained a formal defect related to the inaccuracy of the appearing party’s address data, violating the provisions of Article 38 section (3) point (a) of Law Number 2 of 2014. These analysis results affirm that reconvention proved an effective procedural law instrument for uncovering and proving legal defects in deeds, obtaining a definitive annulment judgment (nietigverklaring), and contributing to the comprehensive resolution of land ownership disputes. It is concluded that fulfilling requirements for a valid agreement and the formalities of authentic deeds are crucial in land transactions, and reconvention plays an important role in protecting landowner rights and enforcing agrarian legal certainty.